Spiritual Strengthening of Santri Through Therapeutic Da'wah: Studying at Al Faridz Islamic Boarding School in Garut - Ashhab N.A, Nizar (Zona Education Indonesia, 2023)
This study aims to explore the effectiveness of therapeutic da'wah in strengthening the spiritual dimension of students at Al Faridz Islamic Boarding School, Garut. Research methods involve literature studies, case studies, interviews, and questionnaires. The results of the case study show that therapeutic da'wah activities are able to create an environment that supports self-reflection, deeper religious understanding, and increased positive social interaction among students. Supporting factors, including the support of cottage caregivers and the quality of therapeutic da'wah materials, play an important role in the success of the program. However, there are several obstacles such as incompatibility of methods with certain student characteristics and limited resources. The questionnaires showed a high level of satisfaction from the students, while there was a significant improvement in their understanding of aspects of spirituality. Recommendations include improved training of therapeutic da'wah preachers, adjustment of methods, and optimization of resources to expand positive impact. This research contributes to the understanding and development of spiritual reinforcement methods in Islamic boarding schools, relevant for the context of religious education in modern Islamic boarding schools